2006
DOI: 10.1111/j.1365-2648.2006.03817.x
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion for frail older home care clients

Abstract: Home based nursing health promotion, proactively provided to frail older people with chronic health needs, enhances quality of life while not increasing the overall costs of health care. The results underscore the need to re-invest in nursing services for health promotion for older clients receiving home care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
237
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(251 citation statements)
references
References 51 publications
5
237
2
7
Order By: Relevance
“…The mean age of all participants was 79 years, and 69% of the participants were women (supplementary materials/appendix 1). The methodological quality of included trials varied; seven trials (Hall et al 1992;Leveille et al 1998;Mann et al 1999;Dalby et al 2000;Rockwood et al 2000;Chin et al 2001;Phelan et al 2004;Holland et al 2005) were of low quality according to the criteria (van Tulder et al 2003), and seven trials were of high quality (Dalby et al 2000;Stuck et al 2000;van Haastregt et al 2000;Hebert et al 2001;Gill et al 2002Gill et al , 2004Gitlin et al 2006a;b;Markle-Reid et al 2006) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean age of all participants was 79 years, and 69% of the participants were women (supplementary materials/appendix 1). The methodological quality of included trials varied; seven trials (Hall et al 1992;Leveille et al 1998;Mann et al 1999;Dalby et al 2000;Rockwood et al 2000;Chin et al 2001;Phelan et al 2004;Holland et al 2005) were of low quality according to the criteria (van Tulder et al 2003), and seven trials were of high quality (Dalby et al 2000;Stuck et al 2000;van Haastregt et al 2000;Hebert et al 2001;Gill et al 2002Gill et al , 2004Gitlin et al 2006a;b;Markle-Reid et al 2006) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of 19 articles (Hall et al 1992;Leveille et al 1998;Mann et al 1999;Dalby et al 2000;Rockwood et al 2000;Stuck et al 2000;van Haastregt et al 2000;Chin et al 2001;Hebert et al 2001;Chin et al 2002;Gill et al 2002Gill et al , 2004Phelan et al 2004;Holland et al 2005;Gitlin et al 2006a;b;Markle-Reid et al 2006;Bouman et al 2008a, b), all RCTs concerning communitydwelling persons 65 years or older identified as frail, vulnerable, at risk of functional decline, having disabilities or chronic conditions and receiving multi-component HPDP interventions were included for detailed review (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations